The Way You Make Me Feel: Psychological and cerebral responses to music during real-life physical activity. (March 2019) - Bigliassi, Marcelo; Karageorghis, Costas I.; Hoy, George K.; Layne, Georgia S.
Abstract: Background: The brain mechanisms that underlie the psychological effects of auditory stimuli during physical activity are hitherto under-researched; particularly so in ecologically valid settings. The objective of the present experiment was to investigate the effects of two contrasting auditory stimuli conditions on psychological responses and brain activity during an outdoor walking task. Methods: Twenty-four participants were required to walk 400 m at a pace of their choosing and report perceptual (state attention and perceived exertion) and affective (valence, arousal, and perceived enjoyment) outcomes immediately after each exercise bout. Three conditions were administered in a randomised and fully counterbalanced order (control, podcast, and music). State-of-the-art, portable EEG technology was used to facilitate measurement during the walking task. Fast Fourier Transform was used to decompose the brain's electrical activity into different band waves (lower-alpha, upper-alpha, sensorimotor rhythm, and beta). Results: The results indicated that music up-regulated beta waves, led to more dissociative thoughts, induced more positive affective responses, up-regulated arousal, and enhanced perceived enjoyment to a greater degree when compared to control and podcast. Conclusions: Rearrangement of beta frequencies in the brain appears to elicit a more positive emotional state wherein participants are more likely to dissociate from internal sensory signals and focus on task-irrelevant factors. The portable EEG system used in the present study appears to accurately measure electrical activity in the brain during light-intensity physical activities and is effective in reducing electrical artefacts caused by body and cable movements. Highlights: State-of-the-art portable EEG technology was used in the present study. Cerebral mechanisms underlying the effects of music on exercise were investigated. The technology facilitated measurement during an ecologically-valid outdoor task. Music reallocated attention externally and elicited positive affective responses. Music up-regulated beta waves during a self-paced walking task.